Effect of pH-dependent fibrillar structure on enzymatic hydrolysis and bioactivity of nanofibrillated whey protein. (September 2020) - Farrokhi, Flora; Badii, Fojan; Ehsani, Mohammad Reza; Hashemi, Maryam
Abstract: The functional properties of fibrillar protein make them an excellent novel food ingredient. However, for industrial applications, it is necessary to have an insight into their digestibility and bioactivity. Therefore, the objectives of this work were to study the enzymatic hydrolysis and bioactivity of nanofibrillated whey protein isolate (WPI), prepared at 90 °C under acidic condition, followed by pH adjustment to 2, 4, and 6. Fourier transform infrared spectroscopy (FTIR) showed that the secondary structure of protein changed and the intermolecular β-sheets structure was formed over fibrillization. The results showed that by increasing the rate of fibril formation at lower pH level monitored by Thioflavin T (ThT) fluorescence spectrophotometry, the degree of pepsin and trypsin hydrolysis in simulated gastrointestinal environments increased significantly. As the extent of fibrillar structure decreased at higher pH, Diphenyl-picryl hydrazinyl (DPPH) radical scavenging activity and Ferric reducing ⁄ antioxidant power (FRAP) of nanofibrillated WPI hydrolysates were reduced. Likewise, in all samples at different hydrolysis times, the antioxidant activities of pepsin-derived hydrolysates were higher than those of tryptic hydrolyzed samples, which probably was resulted from the increased hydrolyzed peptides with higher antioxidant activity. Overall, these findings may reinforce the applications of nanofibrillated proteins as functional food ingredients. Highlights: Enzymatic hydrolysis of nanofibrillated whey protein is affected by fibril solution pH. Degree of enzymatic hydrolysis increases by increasing the rate of fibril formation. Antioxidant activity of nanofibrillated whey protein hydrolysates is reduced at higher pH.